The Farmer Segmentation Tool: Understanding the diversity of coffee farmers - International Institute of Tropical Agriculture (2019)
The farmer segmentation approach was developed by the IITA research team in collaboration with partners. The approach combines quantitative and qualitative aspects to understanding the diversity of farmers within a community. On-farm resources are identified as well as a farmers’ level of entrepreneurship and willingness to invest in their priority crop. The farmer segmentation process identifies differences in farmers’ ability to invest in Good Agricultural Practices (GAPS) and Climate Smart Agriculture (CSA). Being able to consider the farmers capacity and willingness to implement certain practices informs the design of more manageable sets and sequences of practices.